A novel organic semiconducting material: 2-(3-mesityl-3-methylcyclobutyl)-2-keto-ethyl methacrylate (MCKEMA) - Yakuphanoğlu, Fahrettin; Erol, I (Elsevier, 2004)
The electronic transport and thermal conductivity properties of newly synthesized 2-(3-mesityl-3-methylcyclobutyl)2-keto-ethyl methacrylate (MCKEMA) were investigated by electrical measurements. The conduction mechanism of the MCKEMA was determined by AC conductivity measurements (ACCM) and DC conductivity measurements (DCCM). The low mobility values suggest that charge transport mechanism is hopping conduction mechanism. As a result, the MCKEMA is an organic semiconductor with at room temperature conductivity and activation energy values (sigma(25) = 2.09 x 10(-9) S/cm, E-a = 0.45 eV). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: monomer; organic semiconductor; conductivity